Meningism Look-Alike Annona Muricata (Graviola) Poisoning - Khusairi, Zainul Ikhwan Ahmad; Mohd Ghazali, Mohd Affendi (International Journal of Human and Health Sciences (IJHHS), 2022)
Annona muricata is a member of the Annonaceae family and is a fruit tree with a long history of traditional use. A. muricata, also known as soursop, Graviola and guanabana, is an evergreen plant that is mostly distributed in tropical and subtropical regions of the world. Graviola has very broad medicinal claims and is also widely consumed as food and drinks in the tropics. The plant produces a wide range of secondary chemicals, some already known to be toxic. Concerning this, one case has been reported recently in the Emergency Department (ED), Taiping Hospital who suffered from sudden onset of neurotoxin symptoms after drinking a homemade Graviola leaves juice. He was then presented to ED with the complaint of high-grade fever and altered mental status with other gastrointestinal symptoms such as diarrhoea and vomiting. The patients' health was good before drinking the Graviola drinks. On arrival, he was confused with a sign and symptoms of neurotoxicity, hence the patient was treated initially as meningitis. Blood pressure was in the normal range but the pulse rate was around 120- 130bpm with a spike in temperature (41.8◦C). Neck stiffness was noted with no other neurological deficit. Pupil 3 mm equal bilaterally, while lung and cardiovascular were normal. The abdomen was soft but the discomfort was described as bloated and discomfort upon palpation. The patient was resuscitated with normal saline and an antibiotic was started. He was then admitted to the medical ward and lumbar puncture suggested meningitis. Antibiotic treatment was continued until he was discharged. Therefore, all patients with a history of Graviola neurotoxin symptoms should be admitted. The levels of chemicals found in these leaves need to be studied in detail with relevance to the specific signs and symptoms. This is to provide more accurate and effective medical treatment to patients and prevent more serious complications. International Journal of Human and Health Sciences Supplementary Issue: 2022 Page: S26